Association of common mental disorders and related multimorbidity with subsequent labor market marginalization among refugee and Swedish-born young adults - Chen, Jiaying; Mittendorfer-Rutz, Ellenor; Berg, Lisa; Nørredam, Marie; Sijbrandij, Marit; Klimek, Peter (Frontiers in Public Health, 2023)
Background: Common mental disorders (CMDs), multimorbidity, and refugee status are associated with poor labor market outcome. Little is known about how these factors interact in young adults. Objective: We aimed to i) investigate whether the association of CMDs and multimorbidity with labor market marginalization (LMM) differs between refugee and Swedish-born young adults and ii) identify diagnostic groups with particularly high risk for LMM. Methods: This longitudinal registry-based study included individuals aged 20 – 25 years followed from 2012 to 2016 in Sweden (41,516 refugees and 207,729 age and sex-matched Swedish-born individuals). LMM was defined as granted disability pension (DP) or > 180 days of unemployment (UE). A disease co-occurrence network was constructed for all diagnostic groups from 2009 to 2011 to derive a personalized multimorbidity score for LMM. Multivariate logistic regression was used to estimate odds ratios of LMM in refugee and Swedish-born youth as a function of their multimorbidity score. The relative risk (RR, 95% CI) of LMM for refugees with CMDs compared to Swedish-born with CMDs was computed in each diagnostic group. Results: In total, 5.5% of refugees and 7.2% of Swedish-born with CMDs were granted DP; 22.2% and 9.4% respectively received UE benefit during follow-up. While both CMDs and multimorbidity independently elevated the risk of DP considerably in Swedish-born, CMDs but not multimorbidity elevated the risk of UE. Regarding UE in refugees, multimorbidity with the presence of CMDs showed stronger estimates. Multimorbidity interacted with refugee status toward UE (p < 0.0001) and with CMDs toward DP (p = 0.0049). Two diagnostic groups that demonstrated particularly high RR of UE were schizophrenia, schizotypal and delusional disorders (RR [95% CI]: 3.46 [1.77,6.75]), and behavioural syndromes (RR [95% CI]: 3.41 [1.90,6.10]). Conclusion: To combat LMM, public health measures and intervention strategies need to be tailored to young adults based on their CMDs, multimorbidity, and refugee status.